Penerapan Keamanan dan Sanitasi Pangan pada Produksi Nuget dengan Metode HACCP - Dian Rizkina; Aji Jumiono (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2026)
Food safety and sanitation are essential components in the frozen food industry, particularly among Micro, Small, and Medium Enterprises (MSMEs). This study evaluates the implementation of the Hazard Analysis Critical Control Point (HACCP) system in a chicken nugget-producing MSME located in Bogor, Indonesia. A qualitative descriptive approach was applied through direct observations, in-depth interviews, and document analysis. The production process was examined from raw material handling to packaging and distribution. Two Critical Control Points (CCPs) were identified: the cooking stage and the quick freezing process. Monitoring of CCPs involved the use of digital thermometers, timers, and standardized checklists, supported by routine calibration and documentation. Verification measures included internal audits, microbiological testing, and systematic documentation reviews. The consistent application of Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP) was evident throughout the facility. Findings demonstrate that MSMEs, when supported by structured operational procedures and adequate training, are capable of implementing an effective HACCP-based food safety system. This contributes to product quality assurance, consumer protection, and enhanced competitiveness in the processed food sector.